IMPLEMENTASI PERLINDUNGAN PENGETAHUAN TRADISIONAL DI AFRIKA SELATAN - Hafni Harahap, Sartika Fauziah (Universitas Borneo Tarakan, 2022)
Abstract This article discusses the implementation of the protection of traditional knowledge in South Africa with the aim of safeguarding and valuing traditional knowledge as an integral part of the cultural heritage and identity of indigenous communities. The background of this writing includes an overview of traditional knowledge in South Africa and the challenges it faces, including theft, exploitation, and lack of legal recognition. The research methods used are document analysis and literature studies to gather information and data related to the implementation of the protection of traditional knowledge in South Africa. The research findings indicate that the South African government has adopted the Intellectual Property Rights Act to provide a strong legal framework for protecting traditional knowledge and the intellectualrights of indigenous communities. In addition, the establishment of specialized institutions and committees has also taken place to handle the protection of traditional knowledge. Despite these steps that have been taken, challenges such as theft and exploitation of traditional knowledge still exist. The implementation of the protection of traditional knowledge in South Africa is crucial to maintaining cultural sustainability, protecting the rights of indigenous communities, and achieving social and economic justice. Despite the remaining challenges, the steps taken through laws, institutions, and civil society participation demonstrate a commitment to protecting and valuing traditional knowledge as an integral part of South Africa's identity and cultural heritage.Keywords: South Africa, Intellectual Property Rights, Traditional Knowledge, Protection